Cell type mapping reveals tissue niches and interactions in subcortical multiple sclerosis lesions - Lerma Martin, Celia; Badia-i-Mompel, Pau; Ramirez Flores, Ricardo O.; Sekol, Patricia; Schäfer, Philipp; Riedl, Christian J.; Hofmann, Annika; Thäwel, Thomas; Wünnemann, Florian; Ibarra-Arellano, Miguel A.; Trobisch, Tim; Eisele, Philipp; et al. (Nature neuroscience, 2024)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system. Inflammation is gradually compartmentalized and restricted to specific tissue niches such as the lesion rim. However, the precise cell type composition of such niches, their interactions and changes between chronic active and inactive stages are incompletely understood. We used single-nucleus and spatial transcriptomics from subcortical MS and corresponding control tissues to map cell types and associated pathways to lesion and nonlesion areas. We identified niches such as perivascular spaces, the inflamed lesion rim or the lesion core that are associated with the glial scar and a cilia-forming astrocyte subtype. Focusing on the inflamed rim of chronic active lesions, we uncovered cell-cell communication events between myeloid, endothelial and glial cell types. Our results provide insight into the cellular composition, multicellular programs and intercellular communication in tissue niches along the conversion from a homeostatic to a dysfunctional state underlying lesion progression in MS.